Does custody law affect family behavior in and out of marriage? - René Böheim; Mario Francesconi; Martin Halla (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2012)
We examine the effect of joint custody on marriage, divorce, fertility and female employment in Austria using individual-level administrative data, covering the entire population. We also use unique data obtained from court records to analyze the effect on post-divorce outcomes. Our estimates show that joint custody significantly reduces divorce and female employment rates, significantly increases marriage and marital birth rates, and leads to a substantial increase in the total money transfer received by mothers after divorce. We interpret these results as evidence against Becker-Coase bargains and in support of a mechanism driven by a resource redistribution that favors men giving them greater incentives to invest in marriage specific capital.
Keywords: J12; J13; J18; K36; N32; R2; 330; Divorce; Fertility; Bargaining; Intrahousehold Allocations; Austria